Characterization of Chitosan Nanoparticles from Milkfish Scales as an Alternative Preservatives of Fresh Pangas Catfish (Pangasius hypopthalmus) - Zurrotul Ilmiyah; Jamilatur Rohmah (Universitas Muhammadiyah Sidoarjo, 2020)
Fish is a commodities that are very easy to decompose (Highly Perishable), therefore made efforts to extend the shelf life of fish by using preservatives. Preservatives that are not harmful to health are chitosan nanoparticles. The aim of this research are to know the characterization of chitosan nanoparticles from milkfish scales and their effect as fresh pangas catfish preservative by using concentration variation 1%, 2%, 3%, 4%, and 5% and optimization of storage time 12, 24, 36 , 48, 60, and 72 hours. Design in this research is experimental laboratory. Characterization of chitosan nanoparticles using FT-IT and SEM-EDX. While the effect of fresh pangas catfish preservation on chitosan nanoparticles is based on water, ash, protein, and ALT parameters. The results obtained on the characterization of chitosan nanoparticles on the identification of functional groups (FT-IR) showed absorption bands of OH groups at a peak 3450,99 cm-1, the CN snow absorption band was seen at the peak 2360,44 cm-1, the amine band of NH amine at the peak of 1639,20 cm-1 and the crystalline alcohol CO uptake band was observed at a peak of 1096,33 cm-1. The characterization results of SEM-EDX chitosan nanoparticles are round but clumped and clearly visible particle size changes. The experimental results were analyzed with two-way ANOVA statistic showing a significant effect between concentration variation and length of storage time to extend the durability of fresh pangas catfish. The best results of chitosan nanoparticles on fresh pangas catfish is at 5% concentrations at 72 hours of storage time with water value 16,4%, ash value 0,04%, protein value 0,04%, and ALT value 4,0 x 105cfu/g.